2011
DOI: 10.2139/ssrn.2973766
|View full text |Cite
|
Sign up to set email alerts
|

Low Quality Education as a Poverty Trap

Abstract: The weak quality of education received by most poor children in South Africa places them in permanent disadvantage relative to those attending the mainly more affluent and better performing schools. This document draws from a large number of studies undertaken for a major project and summarises this evidence, which illustrating that low quality schools act as a poverty trap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 7 publications
(5 reference statements)
1
46
0
2
Order By: Relevance
“…363 for the former group as compared to 262 for the other group, emphasising the link between disadvantage and poor performance. This correlation is confirmed by Van der Berg et al, (2011) 2008: 8-10). In spite of the apparent commitment of DBE to libraries, the state of school libraries in South Africa, and therefore the provision of suitable reading material, is a source of great concern to the LIS sector.…”
Section: Introductionmentioning
confidence: 57%
“…363 for the former group as compared to 262 for the other group, emphasising the link between disadvantage and poor performance. This correlation is confirmed by Van der Berg et al, (2011) 2008: 8-10). In spite of the apparent commitment of DBE to libraries, the state of school libraries in South Africa, and therefore the provision of suitable reading material, is a source of great concern to the LIS sector.…”
Section: Introductionmentioning
confidence: 57%
“…Studies have shown that South Africa's quality of education lags far behind that of international peers and many of their African neighbours ( Van der Berg, et al, 2011). Social conversion factors could also play a role.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has highlighted the poor state of education in South Africa, which is characterized by under-performing schools and children with extremely low skill levels (Reddy 2006;Fleisch 2008;Fleisch and Schindler 2008;Spaull 2011;Van der Berg et al 2011). Simultaneously, the schooling system is also known for the highly variable resource levels enjoyed by different schools within the public sector and the enormous variations in school performance that tend to accompany this.…”
Section: School Choice and Learner Mobility In South Africamentioning
confidence: 99%
“…Under Apartheid's Bantu Education Act (1953), children's educational opportunities, along with the resources devoted to these, were determined entirely by their racial categorization (Motala 1995;Fedderke, de Kadt, and Luiz 2000;Motala, Dieltiens, and Sayed 2009). While this policy is now a thing of the past, it has left behind a persistent set of geographically defined inequalities in educational infrastructure and resources, with well-performing schools typically located in historically white 1 areas 2 Ladd 2004, 2005;Woolman and Fleisch 2006;Spaull 2011;Van der Berg et al 2011).…”
Section: School Choice and Learner Mobility In South Africamentioning
confidence: 99%